The Conflict Between the Emirs of the State of Nur ad-Din Zangi and Saladin Ayyubi, and the Position of the Abbasid Caliphate On It: الصراع بين أمراء الدولة النورية بقيادة نور الدين زنكي وصلاح الدين الأيوبي، وموقف الخلافة العباسية منه - Nasser Abdullah Nasser Salah; Amer Abdulwahab Mahyoub Murshed; Abdul Hamid, Faisal@Ahmad Faisal (Journal Al-Muqaddimah, 2025)
The study examines the nature of the relationship between the state of Nur ad-Din Zangi and Saladin Ayyubi, and the position of the Abbasid Caliphate on their conflict. The study’s problem lies in how the Abbasid Caliphate dealt with disputes between its nominally subordinate but effectively independent kingdoms, such as the conflict between the Zangids and Saladin Ayyubi. The research discusses the relationship between the Zangids and the Abbasid Caliphate, the reasons for the discord between Nur ad-Din Zangi and Saladin Ayyubi, and the role of the Abbasid Caliphate in this conflict. The findings indicate that the Abbasid Caliphate adopted an ambiguous stance towards the conflict, seeking to achieve its political interests without losing any of the conflicting parties. The study also shows that the Abbasid Caliphate aimed to limit Saladin Ayyubi’s influence while maintaining some rights for the Zangids, reflecting the complexity of political relations during that period. Additionally, the study reveals that the Abbasid Caliphate tried to maintain a balance of power among the conflicting parties to achieve relative political stability.